Master’s degree and job market: possibilities and incongruities - Braquehais, Adna Ribeiro (2005)
The work aimed at investigating, through the eyes of postgraduate nurses and postgraduate students of Nursing, their possibilities and incongruities before the job market in Nursing. It is a descriptive study developed with 10 nurses who were either engaged in a Master’s degree program or already held a Master’s degree or a Doctorate, in the Department of Nursing at UFC. The data were collected in April of 2002, through semi-structured interviews. The analysis of data allowed us to attest that the possibilities conveyed by the Master’s degree are: ‘Possibilities of amplification of knowledge’, ‘Possibilities of competing in selection processes’, ‘Possibilities of contributing to more effective changes in the professional domain’. The expectations about the job market were: ‘Better acceptance’, ‘Work opportunities and compatible remuneration’, ‘Amplified opportunities and valorization of research’. In what concerns the reason for the expectations to be fulfilled or not fulfilled: ‘I got better practice, amplified vision, independence towards learning’, ‘there is a lack of funding institutions’ and, finally, absorption of the postgraduate nurses’ demand in the job market: ‘Larger absorption in the private sector’, ‘Lack of selection processes in universities with great demand of postgraduate professionals’. It has been concluded that the majority of the expectations has been fulfilled, but there is still dissatisfaction regarding professional appraisal through compatible salary, as well as lack of selection processes to absorb these professionals.